Global, regional, and national burden of endocrine, metabolic, blood, and immune disorders from 1990 to 2021, and projections to 2050: a systematic analysis of the global burden of disease study - Liang, Jinpai; Leng, Hongyan; Bai, Xuelian; Li, Linling; Qin, Tao; Ruan, Jiazhi; Wang, Guoxing; Zhang, Wenjuan (Frontiers in Endocrinology, 2025)
BackgroundEndocrine, metabolic, blood, and immune disorders (EMBID) are a leading cause of morbidity and mortality worldwide, with substantial regional disparities. Despite advancements in diagnosis and treatment, the burden of EMBID continues to rise. This study aimed to comprehensively assess the global, regional, and national burden of EMBID from 1990 to 2021, with projections to 2050.MethodsWe conducted a systematic analysis using data from the GBD 2021, covering 204 countries and territories, 21 GBD regions, and five Socio-demographic Index (SDI) groups. Age-standardized rates of incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for EMBID were estimated using the GBD analytical framework. Temporal trends were assessed using estimated annual percentage change (EAPC) derived from log-linear regression. Bayesian age-period-cohort (BAPC) models were applied for projections to 2050. Decomposition analysis attributed changes in disease burden to population growth, aging, and epidemiological shifts.ResultsIn 2021, the global incidence of EMBID was 79.47 million (95% UI 63.34–98.63 million), with an age-standardized rate of 957.58 (95% UI 766.99–1,183.95) per 100,000, showing a slight decline (EAPC: -0.24% [95% CI -0.35 – -0.12]). Prevalence reached 475.78 million (95% UI 381.23–591.19 million), while deaths rose to 175,902 (95% UI 154,306–190,755; EAPC: 0.75% [95% CI 0.67–0.83]). DALYs totaled 12.86 million (95% UI 9.94–16.98 million), with an age-standardized rate of 157.66 (95% UI 122.38–206.92) per 100,000 (EAPC: -0.09% [95% CI -0.16 – -0.02]). Females had higher incidence and prevalence, while males showed higher mortality. Older adults (≥70 years) experienced the highest burden. Decomposition analysis attributed rising DALYs to population aging (26.02%) and growth (85.83%). Regionally, high-SDI regions showed declining incidence, while low-SDI regions had limited progress. Projections to 2050 indicate declining incidence and prevalence but rising mortality among older adults.ConclusionThe global burden of EMBID has demonstrated substantial geographical and temporal variability, with lower-SDI regions bearing the highest burden. Addressing these disparities requires enhanced preventive measures, improved healthcare access, and targeted interventions, particularly in low- and middle-income countries.